2014
DOI: 10.7870/cjcmh-2014-018
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Punitive Violence: Preliminary Data on the Positive Discipline in Everyday Parenting (PDEP) Program

Abstract: Most physical violence against children is punitive in intent. the united nations has called for the elimination of physical punishment of children and for the development of programs teaching nonviolent resolution of parent-child conflict. a focused effort is required to shift entrenched, intergenerationally transmitted, and culturally normalized belief systems about physical punishment. positive discipline in everyday parenting (pdep) was developed to meet this need. its short-term objectives are to: 1) redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 18 publications
4
25
0
3
Order By: Relevance
“…Our findings support those of an ever-growing number of studies that use of CP may lead eventually to the emergence of conduct disorders in children (Gershoff & Grogan-Kaylor, 2016). They also support the recommendations of a growing number of professional and organizations suggesting that prevention and intervention programs be implemented to eliminate CP (Durrant et al, 2004;Fortson et al, 2016) and foster positive, supportive, and autonomy-promoting parent-child relationships (e.g., Smith, Brown, Feldgaier, & Lee, 2015;Durrant et al, 2014). Such programs may help reduce the risk of developing or maintaining child physical aggression and conduct problems (Durrant et al, 2014).…”
Section: Practical Implicationssupporting
confidence: 86%
See 1 more Smart Citation
“…Our findings support those of an ever-growing number of studies that use of CP may lead eventually to the emergence of conduct disorders in children (Gershoff & Grogan-Kaylor, 2016). They also support the recommendations of a growing number of professional and organizations suggesting that prevention and intervention programs be implemented to eliminate CP (Durrant et al, 2004;Fortson et al, 2016) and foster positive, supportive, and autonomy-promoting parent-child relationships (e.g., Smith, Brown, Feldgaier, & Lee, 2015;Durrant et al, 2014). Such programs may help reduce the risk of developing or maintaining child physical aggression and conduct problems (Durrant et al, 2014).…”
Section: Practical Implicationssupporting
confidence: 86%
“…They also support the recommendations of a growing number of professional and organizations suggesting that prevention and intervention programs be implemented to eliminate CP (Durrant et al, 2004;Fortson et al, 2016) and foster positive, supportive, and autonomy-promoting parent-child relationships (e.g., Smith, Brown, Feldgaier, & Lee, 2015;Durrant et al, 2014). Such programs may help reduce the risk of developing or maintaining child physical aggression and conduct problems (Durrant et al, 2014). Our findings also suggest that it may be helpful to screen parents for signs of depression; daughters of depressive mothers may be at particular risk for aggression (citation).…”
Section: Practical Implicationssupporting
confidence: 62%
“…This study evaluated 56 parental education interventions, including programs with a flexible and structured format. The structured interventions included six programs: Incredible Years, Strengthening Families, Personal and Family Support Program, More Family, In Search of the Treasure of Families, and Mission C. Table 2 shows that in 11 studies the participants were parents, including mothers and fathers (Begle & Dumas, 2011;Byrne et al, 2014;Byrne, Salmela-Aro, Read, & Rodrigo, 2012;Durrant et al, 2014;Fetsch, Yang, & Pettit, 2008;Heinrichs et al, 2014;Maalouf & Campello, 2014;Malti, Ribeaud, & Eisner, 2011;Portwood, Lambert, Abrams, & Nelson, 2011;Renzaho & Vignjevic, 2011;Weymouth & Howe, 2011). The parenting program was conducted with caregivers, including mothers, fathers, and other family members, in nine studies (Almeida et al, 2012;Burkhart, Knox, & Brockmyer, 2013;Conner & Fraser, 2011;Knox, Burkhart, & Cromly, 2013;Knox, Burkhart, & Howe, 2011;Knox, Burkhart, & Hunter, 2010;Knox & Burkhart, 2014;Marcynyszyn, Maher, & Corwin, 2011;Prinz, Sanders, Shapiro, Whitaker, & Lutzker, 2009).…”
Section: Types Of Parenting Educational Programsmentioning
confidence: 99%
“…The participants in the 123Magic program also presented significant improvements in parenting stress and self-efficacy (Kendall et al, 2013). Parents who completed the Positive Discipline in Everyday Parenting Program were less supportive of physical punishment, less likely to attribute typical child behaviors to "misbehavior" on the part of the child (e.g., defiance and disrespect), and more likely to believe that they have the skills that are necessary to be good parents from pre-to post-intervention (Durrant et al, 2014).…”
Section: Parent Outcomesmentioning
confidence: 99%
“…The program has been adapted for parents with low levels of literacy, parents who are refugees or immigrants, and parents in a range of cultural, linguistic and faith communities. A pre/post evaluation found significant within-parent-group reduction in approval of physical punishment among a Canadian sample (Durrant et al, 2014). A comparison of pre- and post-test scores across 13 countries (Australia, Canada, Gambia, Georgia, Guatemala, Japan, Kosovo, Mongolia, Palestine, Paraguay, Philippines, the Solomon Islands, and Venezuela) found that, across countries, most parents believed that PDEP will have positive impacts on their parenting and their relationships with their children, and will help them to use less physical punishment (Durrant et al, 2016).…”
Section: Programs Targeting Parentsmentioning
confidence: 99%